(3fVQI GddHGH aj TQM HgLI GdCdHGHs - (3eMeO Hf Ydj GdMejOis; (3YHO GdMdje Hf Shjde RGOg GdbjUQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd Gddjd dHGSkG hGdfgGQ fThQkG hHYO ajbhd GdYHO eMeO Hf GdTjN Ydi GdMejOi de cGfJ HgLI GdCdHGH ai Yde GdESWQdGH ddYGde YHO GdMdje GdbjUQi QSGdI MGhjI degeGJ GdCHhGH s
(3BNQgG (B:s
(3GdHGH GdYTQhf ai eYQbI GdYed HGdchGcH hEPG JhSW djd aGdb eWGdY GdYQhH GdeGVi ai eWGdYI hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs